2017
DOI: 10.1155/2017/3684178
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Regulating Stemness and Differentiation in Embryonal Carcinoma Cells

Abstract: Just over ten years have passed since the seminal Takahashi-Yamanaka paper, and while most attention nowadays is on induced, embryonic, and cancer stem cells, much of the pioneering work arose from studies with embryonal carcinoma cells (ECCs) derived from teratocarcinomas. This original work was broad in scope, but eventually led the way for us to focus on the components involved in the gene regulation of stemness and differentiation. As the name implies, ECCs are malignant in nature, yet maintain the ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 322 publications
(293 reference statements)
0
26
0
2
Order By: Relevance
“…Studies show that extraembryonic trophoblast stem cells preferentially use OXPHOS to produce ATP 18 . However, the metabolic profile of extraembryonic endoderm (XEN) stem cells, which differentiate into primitive (PrE) or parietal endoderm (PE) in a process recapitulated using F9 embryonal carcinoma stem-like cells (F9 cells), remains unknown 19 21 . We reported that F9 cells require increased levels of cytosolic reactive oxygen species (ROS) to differentiate into PrE 22 24 , but the role of the mitochondria, a major source of ROS, has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that extraembryonic trophoblast stem cells preferentially use OXPHOS to produce ATP 18 . However, the metabolic profile of extraembryonic endoderm (XEN) stem cells, which differentiate into primitive (PrE) or parietal endoderm (PE) in a process recapitulated using F9 embryonal carcinoma stem-like cells (F9 cells), remains unknown 19 21 . We reported that F9 cells require increased levels of cytosolic reactive oxygen species (ROS) to differentiate into PrE 22 24 , but the role of the mitochondria, a major source of ROS, has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…RA treatment of F9 cells regulates a plethora of genes (Eifert et al, 2006 ; Su and Gudas, 2008 ; Kelly and Gatie, 2017 ) including Gata6 , which as described earlier plays an integral role in patterning the extraembryonic and embryonic endoderm (Cai et al, 2008 ; Kelly and Drysdale, 2015 ). In F9 cells Gata6 expression increases in response to RA, and when translated it binds to the Wnt6 promoter (Hwang and Kelly, 2012 ).…”
Section: Discussionmentioning
confidence: 91%
“…The mouse blastocyst is comprised of three cell types in preparation for implantation: (1) trophectoderm; (2) pluripotent cells of the inner cell mass; (3) and primitive endoderm (PrE), the initial cell type in the extraembryonic endoderm (ExE) lineage (Kelly and Drysdale, 2015 ). Elucidating the differentiation of these lineages is difficult to study in vivo , and for that reason there are alternative in vitro models including the F9 teratocarcinoma cell line that can be chemically induced by retinoic acid (RA) to differentiate into ExE-like cell types (Kelly and Gatie, 2017 ). Although much is known regarding the differentiation of F9 cells into ExE lineages, an understanding of the signaling mechanism(s) is far from complete.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of RA-induced differentiation of EC and ES cells have been studied extensively [ 30 , 49 , 61 67 ]. To investigate the possible mechanisms underlying various tumor and differentiation potentials of ES R1 and EC F9 cells, we focused on TGF β family factors that play a key role in the regulation of lineage fate during the early development and the earliest stages of pluripotent stem cell differentiation [ 68 70 ].…”
Section: Discussionmentioning
confidence: 99%